Population structure and genetic characteristics of Streptococcus pneumoniae isolates from children with chronic respiratory diseases - Komyagina T.M.; Tryapochkina A.S.; Alyabieva N.M.; Lazareva A.V.; Gorinova Yu.V.; Simonova O.I. (Клиническая микробиология и антимикробная химиотерапия)
Objective.